New cold seep sites on the continental slope southwest to Svalbard - Bellec, V. K.; Chand, S.; Knies, J.; Bjarnadóttir, L. R.; Lepland, A.; Sen, A.; Thorsnes, T. (Frontiers in Earth Science, 2024)
We discovered seafloor features such as bacterial mats and carbonate crusts typical for active methane seeps on the continental slope southwest of Svalbard. These features are associated with two main northwest-southeast trending morphological structures that are oriented parallel to the regional continental slope. Both structures occur at c. 800 m water depth, at the boundary between the Storfjorden trough mouth fan to the south and the Hornsund trough mouth fan to the north, which suggests a loading related fluid seepage. The main structure displays depressions and ridges forming a crater in its center. Other occurring features include small sediment mounds, domes often covered by bacterial mats, and hummocky seafloor colonized by siboglinid tubeworms. Free gas bubbles were spotted close to the centre and plumes along the rims of the structure. Thick carbonate crusts indicate a long seepage history in the center of the structure and on top of the ridges. The sources of the seeps are likely to be Miocene old organic-rich deposits, or Paleocene hydrocarbon reservoirs.